2020
DOI: 10.1016/j.cegh.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of intestinal parasite infections in Mazandaran province, North of Iran

Abstract: Background: Intestinal parasitic infections (IPIs) are confirmed as major public health problems, worldwide. Northern Iran is highly endemic area for such infections. This research aimed to study on the prevalence of IPIs among people referred to the health care centers in Mazandaran Province, Northern Iran. Methods: In this descriptive cross-sectional survey, 984 stool samples were collected during 2015-2016. Fresh stool samples were collected from all individuals and examined by direct slide smear, formalin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
4
0
2
Order By: Relevance
“…The results of the current study reported a prevalence of 0.04% for helminthic infection. The prevalence of intestinal helminthiasis in various parts of Iran has been reported 0-5.8% that is consistent with the findings of the present study (Asgari et al 2003;Rezaiian et al 2004;Daryani et al 2012;Gholipoor et al 2019). H. nana, E. vermicularis, and S. stercoralis were reported as the parasitic helminths in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current study reported a prevalence of 0.04% for helminthic infection. The prevalence of intestinal helminthiasis in various parts of Iran has been reported 0-5.8% that is consistent with the findings of the present study (Asgari et al 2003;Rezaiian et al 2004;Daryani et al 2012;Gholipoor et al 2019). H. nana, E. vermicularis, and S. stercoralis were reported as the parasitic helminths in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…y la giardiasis (G. lamblia), lo que puede comprobarse por el predominio de las amebas encontradas en este estudio en el grupo de niños con diarrea, a pesar de que no todas las amebas identificadas se consideran patógenas. nacional e internacional (25,34,(45)(46)(47) en los que se ha encontrado que los parásitos intestinales están asociados principalmente a las malas condiciones higiénicas, el escaso saneamiento del entorno y la precariedad socioeconómica de las familias.…”
Section: Discussionunclassified
“…Según la escala de Graffar, en el estrato V, el tipo de vivienda corresponde a un rancho con condiciones sanitarias marcadamente inadecuadas. Estos resultados coinciden con los de otros estudios a nivel nacional e internacional 25 , 34 , 45 - 47 ) en los que se ha encontrado que los parásitos intestinales están asociados principalmente a las malas condiciones higiénicas, el escaso saneamiento del entorno y la precariedad socioeconómica de las familias.…”
Section: Discussionunclassified
“…Based on the extracted data from literature, income [ 82 ], animal contact [ 83 ], family size [ 37 ], nutritional status [ 24 , 84 ], age [ 85 ], gender [ 86 ], occupation statue [ 81 ], and some other cases, such as sexual act [ 87 ], genetic and immunity system of host [ 67 , 74 ] were considered as the most effective factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the larger communities need to have better management for water supply and sanitary disposal of wastes and wastewater [ 45 , 74 ]. These goals require appropriate infrastructure, which is largely related to government policy and economics [ 63 , 85 , 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%